PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMENPADA PT JUMBO SWALAYAN MANADO - VELNAWATY K.L. OHY; Johny A. F. Kalangi; Joula J. Rogahang (JURNAL ADMINISTRASI BISNIS, 2017)
Customer satisfaction is also one of the important things in a marketing. When a customerfeels satisfied with a product or service, then customers generally will continue to buy anduse it. And indirectly he will promote by telling others about his experience of the quality ofthe products or services he has used. Conversely, if customers are not satisfied then tend tomove to another place. This study aims to determine and prove how much influence thequality of service to customer satisfaction at PT Jumbo Swalayan Manado. The population inthis study are consumers who shop at Jumbo Self-service. Samples taken by 50 respondentsby using non prpbability sampling technique with accidental sampling approach, that issampling technique based on chance, that anyone who happened to meet with the researchercan be used as sample if considered suitable. One of the factors that determine the level ofsuccess and quality of the company is the ability of the company in providing services tocustomers. Every business competes to produce the best service quality for its consumers.According to the Parasuraman (in Rambat 2013: 216) the quality of services can be definedas how far the difference between reality and consumer expectations for the services theyreceive. Meanwhile, according to Tjiptono (2007) the quality of service as an effort to meetthe needs and desires of consumers and the accuracy of delivery in the balance of consumerexpectations. Based on the results of research and data analysis, the regression equation isgenerated ie, with the value of determination. This means that consumer satisfaction isinfluenced by the independent variable (service quality) consisting of reliability,responsiveness, assurance, empathy, tangible,, while the rest is heard by variable. Beyond thisstudy is quite small, then the next research is suggested to examine the variables that existoutside the study but have a proportion that the quality of service has a positive andsignificant impact on customer satisfaction at PT Jumbo Swalayan Manado. Given the greaterquality of service impact on customer satisfaction is expected to more companies improveservices to create loyal customers.Keywords: Service Quality, Consumer Satisfaction